Mutagenic effect of native species of the Brazilian Cerrado with anti-ulcerogenic activity - Cardoso, Cássia R. P. [UNESP]; Tubaldini, Flavio Romanini [UNESP]; Rodrigues, Clenilson M. [UNESP]; Rinaldo, Daniel [UNESP]; Severi, Juliana Aparecida [UNESP]; Cólus, Ilce Mara S.; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP] (My University, 2008)
Neea theifera Oerted (Nyctaginaceae), Guapira noxia Linn. (Nyctaginaceae) and Hancornia speciosa Gomes (Apocynaceae) are plant species found in Brazilian Cerrado used popularly for the treatment of gastric ulcers. Here they are assessed for mutagenic activity by analysis of the reverse mutations induced in Salmonella typhimurium strains TA100, TA98, TA102 and TA97a, by extracts of the plants, with and without metabolic activation. Methanol and chloroform extracts of N. theifera and G. noxia and methanolic and aqueous extracts of H. speciosa were tested at five different concentrations. It was found that only the methanolic extract of H. speciosa exhibited a positive mutagenic effect, on strains TA98 and TA100 in the absence of metabolic activation. The phytochemical analysis of the species suggested that condensed tannins are the main compounds responsible for the observed effect.
Keywords: Ames test; Guapira noxia; Hancornia speciosa; Mutagenic activity; Neea theifera; Tannins